Society Treatment and Self Acceptance toward Imperfections in Imperfect - Alyaa Nadia Grafeline (Institute of Research and Community Outreach - Petra Christian University, 2023)
Imperfect is one of the Indonesian comedy films that has gone viral in Indonesia. It tells the story of a woman who works in a beauty company who gets different treatment because her appearance does not meet beauty standards. This research was conducted to reveal how society's attitude treats women who do not comply with beauty standards and to find out Rara's reasons for refusing to follow the beauty standards set by society. This study uses the theory of lookism and sizeism. Where patriarchal values have internalized women to participate in discriminating against Rara or women who do not follow beauty standards. The discrimination Rara received from society was discrimination against body shape, skin color and the way she appeared in public. After following the beauty standards, Rara feels uncomfortable and conflicts often occur between her and those closest to her. Rara decides to refuse to follow the standard of beauty that has been set by society with self-acceptance and seeks her happiness.